Stabilized Feedback Control of Unicycle Mobile Robots. (3rd April 2013) - Amar, Khoukhi; Mohamed, Shahab
In this paper, a stabilized feedback control is designed for a class of unicycle non-holonomic mobile robots. The approach is based on kinematic polar coordinate transformations. The suggested control scheme allows the robot to achieve stabilized near-optimal trajectories, while satisfying the hard constraints of specified initial and final postures (positions and orientations). Simulation experiments showing the effectiveness of the proposed technique are provided and discussed.